The Effect of Motion Lines on Apparent-Motion Correspondence under Dichoptic Presentation. (January 2013) - Ito, Hiroyuki
Motion lines enhance the impression of motion when viewing static/dynamic images. I investigated the binocularity of the motion-enhancing effect in an ambiguous apparent-motion display. Even in the dichoptic presentation condition, the effect of motion lines on apparent-motion correspondence was as strong as that in the monoptic condition. Additionally, there were no effects of stereo-depth separation. These results suggest that the effect of motion lines arises from a higher-level motion-processing mechanism that occurs after integrating information from both eyes.